Multi-omic characterisation of Streptomyces hygroscopicus NRRL 30439: detailed assessment of its secondary metabolic potential. (6th January 2022) - Barry, Craig P.; Gillane, Rosemary; Talbo, Gert H.; Plan, Manual; Palfreyman, Robin; Haber-Stuk, Andrea K; Power, John; Nielsen, Lars K; Marcellin, Esteban
Abstract : A multi-omic approach gives a detailed time-resolved insight into the secondary metabolic capacity of Streptomyces hygroscopicus . Abstract : The emergence of multidrug-resistant pathogenic bacteria creates a demand for novel antibiotics with distinct mechanisms of action. Advances in next-generation genome sequencing promised a paradigm shift in the quest to find new bioactive secondary metabolites. Genome mining has proven successful for predicting putative biosynthetic elements in secondary metabolite superproducers such as Streptomycetes . However, genome mining approaches do not inform whether biosynthetic gene clusters are dormant or active under given culture conditions. Here we show that using a multi-omics approach in combination with antiSMASH, it is possible to assess the secondary metabolic potential of a Streptomyces strain capable of producing mannopeptimycin, an important cyclic peptide effective against Gram-positive infections. The genome of Streptomyces hygroscopicus NRRL 30439 was first sequenced using PacBio RSII to obtain a closed genome. A chemically defined medium was then used to elicit a nutrient stress response in S. hygroscopicus NRRL 30439. Detailed extracellular metabolomics and intracellular proteomics were used to profile and segregate primary and secondary metabolism. Our results demonstrate that the combination of genomics, proteomics and metabolomics enables rapid evaluation of a strain's performance in bioreactors for industrial production of secondary metabolites.